ASSERTIVE TRAINING THROUGH GROUP GUIDANCE TO INCREASE STUDENT RESPONSE IN LEARNING FOR CLASS VIII STUDENTS OF SMP NEGERI 2 MEDANG DERAS - Jamila Jamila; Nurfadillah Z (BRIGHT VISION Journal of Language and Education, 2024)
Responding activities are part of the learning process which is included in student learning activities in class. Many students are just silent and inactive during the learning process in class. Regarding the problem of students' low ability to respond in learning, it has a negative impact on lack of understanding and mastery of learning material and has an impact on student learning outcomes which tend to be low. Group guidance in this research is a process of providing assistance to increase all the potential possessed by a number of individuals and to obtain new information that will be discussed. The aim of this research is to determine the application of group tutoring services to increase student responses in learning for class VIII students at SMP Negeri 2 Medang Sangat for the 2022/2023 academic year. The objects of this research were 7 students in class VIII of SMP Negeri 2 Medangdera who had a tendency to be inactive and did not want to respond to learning. Service implementation is carried out in 2 cycles of group guidance services. The research design in this study is planning, action, observation and reflection. To obtain data and information in this research, observations and interviews were carried out. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the data analysis that has been described. It can be concluded that the group guidance service in cycle 1 for students in class VIII of SMP Negeri 2 Medang Sangat went well, there were several students who showed changes in responding during learning activities, but had not yet reached the good category, in cycle 2 showed changes in attitudes that were even better in responding during learning activities to teachers and friends. Based on the results of observations and interviews conducted in cycles 1 and 2, the researcher stated that group guidance services could increase students' responses to learning.